American Labyrinth : Intellectual History for Complicated Times - Hartman, Andrew; Haberski, Raymond J., 1968- (Book collections on Project MUSE., 2018)
"This volume of essays by 19 intellectual historians of the United States looks at the current state of the field and answers the question, how might the methods of intellectual history shed light on contemporary issues with historical resonance?"--